Implementasi Peraturan Daerah Kota Medan No 6 Tahun 2003 Tentang Larangan Gelandangan Dan Pengemisan Serta Praktek Susila Dikota Medan Dalam Pencegahan Dan Penanggulangan Pekerja Seks Komersial (PSK) - Jefri Panjaitan; Adam Adam; Yurial Arief Lubis (Strukturasi: Jurnal Ilmiah Magister Administrasi Publik, 2022)
The problem in this study is the proliferation of prostitution activities in public places in the city of Medan, such as Jalan Setia Budi, Simpang Selayang Village, Medan Tuntungan District. This study aims to find out how the implementation of the Medan City Regional Regulation No. 6 of 2003 concerning the Prohibition of Homeless and Begging and Immoral Practices in the City of Medan in the prevention and control of Commercial Sex Workers in the city of Medan, especially the Medan Tuntungan sub-district. This study uses the theory put forward by an expert named George C. Edward III, while the type of research used is qualitative research with data collection techniques of observation, interviews, documentation. The following describes the research results, namely 1). Communication, the Regional Government has not created a formal forum to socialize this Regional Regulation and the dangers of prostitution. Many people do not know about the negative impact of prostitution and even the Regional Regulations that regulate it. 2). Resources, lack of facilities and infrastructure Social services . 3). Attitude/disposition, the implementer has given a mandate to the executor, namely the Satpol PP to eradicate sex workers. 4). The bureaucratic structure has coordinated with related parties such as the Satpol PP, the Police and the Health Service, but because the suggestions and infrastructure have not been adequate, execution is difficult. Apart from the absence of a special rehabilitation center for the city of Medan, the uncooperativeness of the sex workers caught in the raids made it difficult for the officers to carry out their obligations.